Low noise amplifier performance study for wireless man based on IEEE 802.16A standard - Mazumil, Mazhaniza (2007)
In a rapid expanding worldwide wireless communications industry today, the demand for Wireless Metropolitan Area Network (WMAN) systems is growing very fast as well. New WMAN system based on IEEE 802.16a standard delivers high data rate with the optional bandwidth, better spectral efficiency, improved performance under multipath fading conditions and less interference in low-mobility wireless conditions than earlier systems. To support high data in the systems multicarrier modulation, Orthogonal Frequency Division Multiplex (OFDM) is used. In practice, component such as low noise amplifier (LNA) should be chosen based on low cost. On the other hand, the effect of non-linear distortion must be considered very carefully because the OFDM system is very sensitive to it. So, the WMAN system must be tested and verified by using measurements so as to see the the system meets the requirements of the IEEE standard. For RF receiver tests in particular, bit error rate (BER) and packet error rate (PER) are required. There are several possible approaches to test the complete WMAN system. However, in this project, a special method that combines test equipment and simulation software has been developed to verify a low noise amplifier (LNA) prototype by measuring the bit error rate (BER) and packet error rate (PER) performance. Comparison has been made between the simulated and tested performances of LNA. The results show that the LNA is within the specification and standard.